Applications of calcium and boron increase yields of Italian tomato hybrids (Solanum lycopersicum) in two growing seasons - Zamban, Débora T.; Prochnow, Daiane; Caron, Braulio O.; Turchetto, Mônica; Fontana, Daniele Cristina; Schmidt, Denise (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 82-93).